The Relationship between Emotional Intelligence and Social Support on Academic Achievement of Students during the COVID-19 Pandemic at SMAN XY Lampung Selatan - Muhammad Lathief Syaifussalam; Rima Wilantika; Andi Musthafa Husain; Meilia Wigati; Raidah Hanifah (CV Media Inti Teknologi, 2024)
This study investigates the correlation between emotional intelligence and social support on academic achievement among high school students. Utilizing a non-experimental quantitative approach with purposive sampling, data were collected from 70 students aged 15-18 years in grades X-XII at SMAN XY Lampung Selatan. Emotional intelligence was assessed using Goleman's Emotional Intelligence Competencies (GEIC), social support was measured with the Multidimensional Scale of Perceived Social Support (MSPSS), and academic performance was evaluated based on the previous semester's scores. Multiple regression analysis revealed that emotional intelligence and social support collectively contribute 68.6% to academic achievement, indicating that 31.4% of the variance is attributable to other factors not examined in this study. Based on the data analysis, emotional intelligence and social support significantly influence students' academic achievement in SMAN XY Lampung Selatan. This research is expected to provide practical contributions for schools, teachers, and parents to train students' emotional intelligence and enhance social support, enabling students to demonstrate optimal academic performance. Theoretical contributions are also anticipated to enrich studies on psychological variables supporting academic achievement in educational psychology.